2014
DOI: 10.1152/ajprenal.00211.2014
|View full text |Cite
|
Sign up to set email alerts
|

ASK1/p38 signaling in renal tubular epithelial cells promotes renal fibrosis in the mouse obstructed kidney

Abstract: Stress-activated kinases p38 MAPK and JNK promote renal fibrosis; however, how the pathways by which these kinases are activated in kidney disease remain poorly defined. Apoptosis signal-regulating kinase 1 (ASK1/MAPKKK5) is a member of the MAPKKK family that can induce activation of p38 and JNK. The present study examined whether ASK1 induces p38/JNK activation and renal fibrosis in unilateral ureteric obstruction (UUO) using wild-type (WT) and Ask1-deficient (Ask1(-/-)) mice. Basal p38 and JNK activation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 52 publications
(68 reference statements)
4
92
0
Order By: Relevance
“…Mice lacking the Ask1 gene (Ask1 2/2 including normal kidney structure and function, which contrasts with the fetal lethality of mice lacking the p38a/ Mapk14 gene (16,17). In addition, Ask1 2/2 mice show a dramatic inhibition of p38 MAPK activation and significant protection from kidney injury in models of acute tubular necrosis and renal interstitial fibrosis, providing results consistent with administration of p38 inhibitors (4,(18)(19)(20). Therefore, inhibition of ASK1/p38 signaling may have therapeutic potential for diabetic glomerulosclerosis.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Mice lacking the Ask1 gene (Ask1 2/2 including normal kidney structure and function, which contrasts with the fetal lethality of mice lacking the p38a/ Mapk14 gene (16,17). In addition, Ask1 2/2 mice show a dramatic inhibition of p38 MAPK activation and significant protection from kidney injury in models of acute tubular necrosis and renal interstitial fibrosis, providing results consistent with administration of p38 inhibitors (4,(18)(19)(20). Therefore, inhibition of ASK1/p38 signaling may have therapeutic potential for diabetic glomerulosclerosis.…”
mentioning
confidence: 80%
“…This is consistent with a role for ASK1 in high glucose-induced p38 activation in cultured glomerular mesangial cells (36) and the various stresses present in diabetes (e.g., oxidative stress, endoplasmic reticular stress, hyperglycemia, and angiotensin II) that are known to activate ASK1/p38 signaling (37). However, activation of p38 MAPK signaling can operate independent of ASK1 in kidney cells as shown by the unaltered lipopolysaccharide and interleukin-1-induced p38 activation and biological responses seen in Ask1 2/2 tubular epithelial cells (4). Thus, ASK1 is a context-dependent regulator of p38 activation, which is particularly important in settings of oxidative stress owing to the regulation of ASK1 activation by antioxidant proteins such as thioredoxin.…”
Section: Diabetesdiabetesjournalsorgmentioning
confidence: 99%
See 1 more Smart Citation
“…MAPKs can be activated in liver fibrosis, increasing Col1α2 transcription [23,24]. The MAPK pathway also plays a key role in myocardial fibrosis, lung fibrosis and renal fibrosis [25][26][27][28]. In normal skin, exogenous TGF-β1 can activate p38, which can combine with the Col1α2 promotor and increase the transcription of Col1α2.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, p38 activation of proximal tubular epithelial cells by astrocyte elevated gene-1 plays an important role in TGF-β1-induced epithelial to mesenchymal transition, which is an important cellular event in organogenesis, cancer and renal tubulointerstitial fibrosis [96]. A member of the MAPKKK family, apoptosis signal-regulating kinase 1, can induce activation of p38 and JNK to promote renal fibrosis in an obstructed mouse kidney [97]. Xu et al showed that increasing the activation of the JNK and p38 pathways plays a prominent role in renal tubular cell apoptosis, which subsequently accelerates the progression of renal tubulointerstitial fibrosis.…”
Section: Com/cpbmentioning
confidence: 99%